The correlation among the Ramsay sedation scale, Richmond agitation sedation scale and Riker sedation agitation scale during midazolam-remifentanil sedation - Namigar,Turgut (2017)
Abstract Background and objectives: Sedative and analgesic treatment administered to critically ill patients need to be regularly assessed to ensure that previously stated goals are well achieved as the risk of complications of oversedation is minimized. We revised and prospectively tested the Ramsay Sedation scale (RSS) for interrater reliability and compared it with the Sedation-Agitation Scale (SAS) and the Richmond Agitation Sedation Scale (RASS) to test construct validity during midazolam-remifentanil sedation. Methods: A convenience sample of ICU patients was simultaneously and independently examined by pairs of trained evaluators by using the revised SAS, RSS, and RASS. Ninety-two ICU patients were examined a total of 276 times by evaluator pairs. Results: The mean patient age was 61.32 ± 18.68 years, 45,7% were female (n = 42), 54.3% male (n = 50). Their APACHE values varied between 3 and 39 with an average of 13.27 ± 7.86 and 75% of the cases were under mechanical ventilation. When classified by using RSS (2.70 ± 1.28), 10.9% were anxious or agitated (RSS1), 68.5% were calm (RSS 2-3), and 20.6% were sedated (RSS 4-6). When classified by using RASS (-0.64 ± 1.58), 20.7% were anxious or agitated (RASS+1 to +4), 63.0% were calm (RASS 0 to -2), and 16.3% were sedated (RASS -3 to -5). When classified by using SAS (2.63 ± 1.00), 12% were anxious or agitated (SAS 5-7), 57.6% were calm (SAS 4), and 30.4% were sedated (SAS 1-3). RSS was correlated with the SAS (r = -0.656, p < 0.001) and RASS was correlated with the SAS (r = 0.565, p < 0.001). RSS was highly correlated with the RASS (r = -0.664, p < 0.001). Conclusions: Ramsay is both reliable and valid (high correlation with the RASS and SAS scales) in assessing agitation and sedation in adult ICU patients.